2022
DOI: 10.3389/fphar.2021.788977
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat (FG-4592) Facilitates Recovery From Renal Damage by Ameliorating Mitochondrial Dysfunction Induced by Folic Acid

Abstract: Incomplete recovery from acute kidney injury induced by folic acid is a major risk factor for progression to chronic kidney disease. Mitochondrial dysfunction has been considered a crucial contributor to maladaptive repair in acute kidney injury. Treatment with FG-4592, an inhibitor of hypoxia inducible factor prolyl-hydroxylase, is emerging as a new approach to attenuate renal damage; however, the underlying mechanism has not been fully elucidated. The current research demonstrated the protective effect of FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…In a rat model of cisplatin‐induced AKI, the expression of claudin‐2, occludin and ZO‐1 was notably decreased togheter with the disturbance in oxygen free radicals and inflammatory cytokines, while the expression of claudin‐5 remained unchanged (Lee et al, 2020; Trujillo et al, 2014). In the murine AKI model induced by folic acid, it was also observed that the expression of ZO‐1 was downregulated (Li et al, 2021b; Zhou et al, 2018). The change was associated with mitochondrial damage, resulting in excessive production of ROS and decreased ATP level, which further induced cell apoptosis and disruption of TJ structure.…”
Section: Tj and Akimentioning
confidence: 98%
See 1 more Smart Citation
“…In a rat model of cisplatin‐induced AKI, the expression of claudin‐2, occludin and ZO‐1 was notably decreased togheter with the disturbance in oxygen free radicals and inflammatory cytokines, while the expression of claudin‐5 remained unchanged (Lee et al, 2020; Trujillo et al, 2014). In the murine AKI model induced by folic acid, it was also observed that the expression of ZO‐1 was downregulated (Li et al, 2021b; Zhou et al, 2018). The change was associated with mitochondrial damage, resulting in excessive production of ROS and decreased ATP level, which further induced cell apoptosis and disruption of TJ structure.…”
Section: Tj and Akimentioning
confidence: 98%
“…Nephrotoxin‐induced AKI : In a murine model of folic acid‐induced AKI, FG‐4592 (Roxadustat) accelerated tubular repair by facilitating the recovery of tubular structural integrity and upregulating expression of ZO‐1 in TECs (Li et al, 2021b). FG‐4592 restored colonic epithelium TJ expression in CKD rats through the upregulation of miR‐223 induced by HIF‐1α (Qu et al, 2022).…”
Section: Tj Proteins As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Roxadustat protects against ischaemia/reperfusion-induced acute kidney injury through inhibiting the mitochondrial damage pathway in mice (Zhang M. et al, 2022). Roxadustat facilitates recovery from renal damage by ameliorating mitochondrial dysfunction induced by folic acid (Li X. et al, 2021). Roxadustat protects against renal ischemia/reperfusion injury by inhibiting inflammation (Miao et al, 2021).…”
Section: Roxadustat and Diabetic Nephropathymentioning
confidence: 99%
“… Huang et al (2020) showed that roxadustat inhibited experimental pulmonary fibrosis by regulating the TGF-β1/Smads signaling pathway in vitro and in vivo . Li et al (2021b) studied a folic acid (FA)-induced AKI model and found that roxadustat pretreatment promoted the regeneration of renal tubular structures 7 days after FA injection. They also found that roxadustat inhibited ferroptosis and inflammation due to activation of Nrf2 by Akt/GSK-3β, thereby inhibiting interstitial fibrosis ( Li et al, 2020b ).…”
Section: Effect Of Roxadustat On Fibrosismentioning
confidence: 99%
“…Although current findings suggest the relationship of ROS and HIF is complex, and even differs in different cells and tissues, no clinical studies of roxadustat have reported elevated ROS levels. In fact, there is evidence that roxadustat reduced ROS production and attenuated FA-induced kidney damage ( Li et al, 2021b ). IRI is the most common cause of acute kidney injury.…”
Section: Effect Of Roxadustat On Oxidative Stressmentioning
confidence: 99%